Periumbilical fat auto-graft associated to a porous orbital implant for socket reconstruction after enucleation. (3rd July 2016) - Medel, Ramon; Alonso, Tirso; Pelaez, Francisco; Vasquez, LuzMaria
ABSTRACT: Having to remove the sclera, fat and the optic nerve in patients undergoing an enucleation, translates in a larger volume that needs to be replaced to achieve good motility and aesthetic results. Using a 20 or 22 mm implant can only partially replace the removed volume. We report the results of our enucleation technique, which includes the use of a porous orbital implant combined with a primary fat graft to replace a higher percentage of the removed volume to achieve a better cosmetic outcome and to avoid implant related complications in high risk patients. Prospective, non-randomized study of enucleated patients for whom porous orbital implantation was performed with anterior placement of a fat auto-graft. The development of implant extrusion or exposure was recorded as well as the presence of conjunctival wound dehiscence and infection. Orbital volume was clinically and radiologically evaluated as well. Twenty-eight patients were included, with a postop follow-up of at least 6 months (6-79 months). No cases of migration or extrusion were found. One case of a large exposure resolved completely. All MRI demonstrated proper implant-graft integration and vascularisation. The aesthetic result and the symmetry were very adequate, with Hertel differences of less than 2 mm in all cases and good motility range. The fat graft is well tolerated, showing low incidence of implant-related complications whilst maintaining good volume and motility.